Dual mobility total hip arthroplasty in hemiplegic patients - Henawy, Ayman T. (SICOT J, 2017)
Introduction: The rate of cerebrovascular insults is increasing, currently leaving many patients with difficulties to maintain their balance due to muscular weakness and/or poor central control. Those patients are at risk of dislocation when total hip arthroplasty (THA) is planned. Instability remains the most significant issue after primary THA especially in such groups of patients. The risk is more pronounced when other factors are added such as, older age, femoral neck fractures, avascular necrosis and/or hip osteoarthritis. Dual mobility cup (DMC) is considered as a prosthesis with higher inherent stability that may help in such situation. In this patient series, we aimed to evaluate stability, clinical and radiological results of dual mobility THA done on the weak limb of hemiplegic patients. Methods: Twenty-four consecutive hemiplegic patients have undergone DMC with a mean age of 68 years. The indication for surgery was hip osteoarthritis in one third of the patients and femoral neck fractures in the remaining patients. Those patients were capable of walking prior to hospital admission despite weakness. Those patients were observed postoperatively for at least one year. Clinical results and complications were recorded. Results: After a minimum of one year, 91.6% of the patients have satisfactory results. No cases of hip or intraprosthetic dislocation were observed. Discussion: Dual mobility THA in the hemiplegic patients provides both efficacy and stability with good functional results.